Multi-wavelength Brillouin fiber laser using a holey fiber and a bismuth-oxide based erbium-doped fiber - Shahi, Sharifeh; Harun, Sulaiman Wadi; Ahmad, Harith (IOP Publishing, 2009)
Multi-wavelength Brillouin fiber laser (BFL) is demonstrated using a holey fiber and a Bismuth-oxide based erbium-doped fiber (Bi-EDF) in a simple ring resonator. The proposed BFL is able to generate up to 13 lines including anti-Stokes with a channel spacing of 0.08 nm at the 1574 nm region. The multi-wavelength BFL is stable at room temperature and also compact due to the use of only a 20 m long of holey fiber and a 215 cm long of Bi-EDF.